2009
DOI: 10.1258/acb.2009.009065
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glomerular filtration rate by serum cystatin C in patients undergoing coronary artery bypass grafting

Abstract: Cystatin C is a better marker for detecting small temporary changes of GFR in CABG patients. This may allow better identification of patients with renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…However since most of those studies did not provide a reference GFR measurement against which SCr and SCysC could be thoroughly compared, the real added value of SCysC as a marker of GFR has remained partly speculative [6]. Among all these studies, only two of them realized after cardiac surgery have measured GFR by a reference method (iohexol or 51 Cr-EDTA) and showed superior performance of cystatin C [18,19]. Focusing specifically on critically ill patients, Le Bricon et al measured GFR by a reference method ( 51 Cr-EDTA) and showed a better correlation between 1/cystatin C and GFR than between 1/creatinine and GFR (r = 0.755 versus r = 0.686).…”
Section: Discussionmentioning
confidence: 99%
“…However since most of those studies did not provide a reference GFR measurement against which SCr and SCysC could be thoroughly compared, the real added value of SCysC as a marker of GFR has remained partly speculative [6]. Among all these studies, only two of them realized after cardiac surgery have measured GFR by a reference method (iohexol or 51 Cr-EDTA) and showed superior performance of cystatin C [18,19]. Focusing specifically on critically ill patients, Le Bricon et al measured GFR by a reference method ( 51 Cr-EDTA) and showed a better correlation between 1/cystatin C and GFR than between 1/creatinine and GFR (r = 0.755 versus r = 0.686).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of adult patients undergoing CS, urinary Cys C was able to detect AKI within 6 h after surgery [23] and serum Cys C had showed to be a better marker for detecting small temporary changes of GFR than sCr or creatinine clearance allowing better identification of patients who developed renal impairment [24]. In a study of 60 patients who underwent heart valve replacement surgery, serum Cys C was superior to creatinine in diagnosing renal dysfunction (AUC 0.876 for Cys C vs. 0.801 for sCr) [22].…”
Section: Novel Renal Biomarkers For Cardio-renal Syndromementioning
confidence: 99%
“…[18-20;28;29] It holds advantages over serum creatinine in that it is unaffected by the demographic characteristics that determine muscle mass and hence serum creatinine level, and its serum levels are also unaffected by tubular secretion. [21;22] Cystatin C has been shown to be a reliable marker of GFR in patients undergoing cardiac surgery, [18][19][20] but its ability to supersede serum creatinine for monitoring changes in GFR in the immediate post-operative period (which is the most important time period for the development of AKI) remains controversial. Some studies have suggested that serum cystatin C may be able to diagnose postoperative AKI more rapidly than serum creatinine, [23] but others have been unable to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Cystatin C is a 13,25 kDa protein produced by all nucleated cells in the human body. [21] It is freely filtered in the glomerulus, then reabsorbed by epithelial cells in the proximal tubule where it is metabolized and not returned to the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%